2019
DOI: 10.1039/c9nr03797g
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating antibacterial activities of graphitic carbon nitride nanosheets with plasma treatment

Abstract: In this study, we have demonstrates that nitrogen-plasma-treated g-C3N4 nanosheet exhibits excellent and broad-spectrum antibacterial activity against eight foodborne pathogens in the absence of light illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 75 publications
0
22
1
Order By: Relevance
“…Additionally, the contribution ratio of different peaks 56 in N 1s and C 1s for GCN and GCN-xTAP (x = 0, 0.25, 0.5, 0.75, 1) according to XPS analysis is shown in Tables S2 and S3. Apparently, the N 3 contents (from 21.63 to 13.97%) of samples are decreased in varying degrees after TAP incorporation, which indicated that the N deficient comes from −NH x .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the contribution ratio of different peaks 56 in N 1s and C 1s for GCN and GCN-xTAP (x = 0, 0.25, 0.5, 0.75, 1) according to XPS analysis is shown in Tables S2 and S3. Apparently, the N 3 contents (from 21.63 to 13.97%) of samples are decreased in varying degrees after TAP incorporation, which indicated that the N deficient comes from −NH x .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, by using the combination of MD simulations and experiments, we discovered that this kind of specific interactions between positively charged groups of bacterial lipid head groups and the C 3 N 4 pores, also weakened the C 3 N 4 insertion into the bacterial membrane due to the strong binding interactions between the lipid head groups and the C 3 N 4 nanomaterial, reflecting the weak antibacterial activity of pristine C 3 N 4 (ref. 40 ). However, after nitrogen plasma treatment, the pores of C 3 N 4 were sealed, endowing the C 3 N 4 nanosheet with a more homogeneous surface that results in an increase in membrane insertion and the concomitant increase in the C 3 N 4 antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, C 3 N 4 was a porous 2D nanomaterial, in the sense that every pore is surrounded by six nitrogen atoms forming a negatively charged center (due to inherent charge transfer from the C atoms to the N atoms). The force field parameters for C 3 N 4 were obtained from our previous study, 40 and the details were shown in Fig. S1.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Under light illumination, g-C 3 N 4 alone and in association with metals/semiconductors inactivated microorganisms through the generation of ROS [31]. Besides having photochemotherapy capabilities, g-C 3 N 4 nanosheets also displayed cytotoxicity by inducing the rupture of the cell membrane of bacteria upon direct mechanical contact [34]. A similar physical mechanism of action is proposed for DNC-based antimicrobial agents [33].…”
Section: Introductionmentioning
confidence: 81%